2011
DOI: 10.1371/journal.pone.0020565
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Analytical Sensitivity by Oligonucleotides Modified with Para- and Ortho-Twisted Intercalating Nucleic Acids – TINA

Abstract: The sensitivity and specificity of clinical diagnostic assays using DNA hybridization techniques are limited by the dissociation of double-stranded DNA (dsDNA) antiparallel duplex helices. This situation can be improved by addition of DNA stabilizing molecules such as nucleic acid intercalators. Here, we report the synthesis of a novel ortho-Twisted Intercalating Nucleic Acid (TINA) amidite utilizing the phosphoramidite approach, and examine the stabilizing effect of ortho- and para-TINA molecules in antiparal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Indeed, although quadruplex 32R-3n or 32R-3n with P insertions is degraded in serum, their analogs with two LNA at the 3′ show a fairly good resistance. Previous studies demonstrated that the introduction of P at the ends of duplex or quadruplex DNA strongly increases the T M (10,75). An interesting effect of TINA ( P or O ) is its capacity to favor an intramolecular folding of the strand in which they have been inserted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although quadruplex 32R-3n or 32R-3n with P insertions is degraded in serum, their analogs with two LNA at the 3′ show a fairly good resistance. Previous studies demonstrated that the introduction of P at the ends of duplex or quadruplex DNA strongly increases the T M (10,75). An interesting effect of TINA ( P or O ) is its capacity to favor an intramolecular folding of the strand in which they have been inserted.…”
Section: Discussionmentioning
confidence: 99%
“…We synthesized aptamer variants with either insertions or replacements of nucleotides by using three different PAHs, namely ortho ‐TINA (O) (( R )‐3‐((2‐(1‐pyrenylethynyl)benzyl)oxy)propane‐1,2‐diol),8 TINA (P) (( R )‐3‐((4‐(1‐pyrenylethynyl)benzyl)oxy)propane‐1,2‐diol) and Amany (Y) (( S )‐4‐(4‐(1 H ‐phenanthro[9,10‐d]imidazol‐2‐yl)phenoxy)butane‐1,2‐diol)9 (Scheme ). We then assessed their inhibitory potential by measuring their impact on routine plasma‐based coagulation assays, such as the thrombin time and the activated partial thromboplastin time.…”
Section: Methodsmentioning
confidence: 99%
“…It stacks with the nucleobases by its aromatic ring and its stabilizing ability is much dependant on where it is placed in an ON sequence. For instance, when placed terminally, both ortho and para-TINA (figure 4E+F) gave higher stability for an antiparallel duplex compared to when placed at other positions (166).…”
Section: Intercalators and Dna Ligandsmentioning
confidence: 99%